2023
DOI: 10.3390/su151410932
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Comfort, Growth Performance and Welfare of Olive Pulp Fed Broilers during Hot Season

Abstract: This study evaluated the nutritional effect of dried olive pulp (OP), on broilers’ thermal comfort, growth parameters and welfare in a commercial poultry farm during the hot season. A number of 108 Cobb male broilers, 19 d olds were allocated into three dietary groups: controls (CON), OP3 and OP6, based on the level of OP added to their diet (0%, 3% and 6%). The thermal comfort of broilers was assessed using the temperature–humidity index (THI). Broilers’ body temperature (BT) was determined weekly. OP benefic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 74 publications
0
3
0
Order By: Relevance
“…The average minimum and maximum recorded brooding temperature in the present study were 30 and 35 • C, respectively, which is considered the critical temperature zone (26-35 • C) for growing broilers [44,45]. Moreover, the current calculated THI values averaged from 29 to 33.8, which was classified as severe to very severe heat stress [28]. The premier factor for impaired performance of chickens is the drop in feed intake observed under heat stress.…”
Section: Discussionmentioning
confidence: 58%
“…The average minimum and maximum recorded brooding temperature in the present study were 30 and 35 • C, respectively, which is considered the critical temperature zone (26-35 • C) for growing broilers [44,45]. Moreover, the current calculated THI values averaged from 29 to 33.8, which was classified as severe to very severe heat stress [28]. The premier factor for impaired performance of chickens is the drop in feed intake observed under heat stress.…”
Section: Discussionmentioning
confidence: 58%
“…This work investigates the antioxidant action of OL in the hepatic of broilers, an organ responsible for the homeostasis of the entire organism and simply exposed to oxidative stress ( Tufarelli et al, 2016 ). In the study of Dedousi et al (2023) , it was observed that the dietary inclusion of dried olive pulp ( DOP ) during hot climates significantly improved broiler growth performance. An encouraging impact on the well-being of chickens was observed in terms of feather cleanliness and panting behavior when chickens were fed a diet containing 6% OP ( Dedousi et al, 2023 ).…”
Section: Struggling With Thermal Stress Effectsmentioning
confidence: 99%
“…In the study of Dedousi et al (2023) , it was observed that the dietary inclusion of dried olive pulp ( DOP ) during hot climates significantly improved broiler growth performance. An encouraging impact on the well-being of chickens was observed in terms of feather cleanliness and panting behavior when chickens were fed a diet containing 6% OP ( Dedousi et al, 2023 ). Using OP as a feed ingredient shows promise as a feeding approach to mitigate the negative consequences of heat stress.…”
Section: Struggling With Thermal Stress Effectsmentioning
confidence: 99%